2020
DOI: 10.1111/tri.13605
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative calculation of the tacrolimus concentration‐to‐dose ratio does not predict outcomes after kidney transplantation

Abstract: There is an emerging interest in the tacrolimus metabolism rate as it is linked to outcomes after transplantation [1][2][3][4][5][6][7]. We and others propose the concentration-to-dose (C/D) ratio as a simple surrogate for the individual tacrolimus (Tac) metabolism rate [5,8,9]. Recently, Jouve et al. [3] showed in a large retrospective singlecenter study that the C/D ratio was in contrast to the CYP3A5 genotype strongly associated with outcomes after renal transplantation (RTx). They used a C/D ratio cutoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The choice of the 3 month time point for the calculation of the C/D ratio was a compromise. We already know from previous analyses that the calculation of the C/D ratio at very early time points (postoperative day 1-10) is not able to predict the metabolism type at all [32]. However, we found acceptable correlations between the 3 month time point and the calculation at 1 month or 6 months [7].…”
Section: Discussionmentioning
confidence: 44%
“…The choice of the 3 month time point for the calculation of the C/D ratio was a compromise. We already know from previous analyses that the calculation of the C/D ratio at very early time points (postoperative day 1-10) is not able to predict the metabolism type at all [32]. However, we found acceptable correlations between the 3 month time point and the calculation at 1 month or 6 months [7].…”
Section: Discussionmentioning
confidence: 44%
“…32 However, studies involving European cohorts of renal allograft recipients found no significant association between CYP3A5 gene variant and either allograft survival or the occurrence of biopsy-proven rejection. 9,24,[41][42][43] A significantly higher rate of acute rejection events was found in Asian cohorts and may be due to the higher frequency of the expresser allele among Asians. 24,42 Accordingly, the previously published results of a meta-analysis pooling 25 studies of the association between CYP3A5 genotype and the risk of acute rejection found no significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Low CDR has been associated with CNI toxicity, BK viremia, decreased allograft function, and an independent risk factor for DCGL (11,13,31). In contrast, some studies have reported that low CDR is not a significant risk factor for adverse allograft outcomes, such as BPAR and DCGL (15,16). In the present study, a low CDR itself was not observed as an independent risk factor for DCGL when other confounding factors (TAC-C0-TWA, TAC-C0-TWCV, age, and induction regimen, Supplemental Table 4) were adjusted (HR 1.66, 95% confidence interval 0.73-3.76).…”
Section: B Amentioning
confidence: 99%
“…Several recent studies on CDR have reported that RM is a significant factor affecting the prognosis of KT recipients ( 11 , 13 ). However, some studies have also reported that CDR is not a significant factor influencing allograft outcomes; therefore, the importance of CDR in KT remains controversial ( 15 , 16 ). In patients showing high IPV in RM status, fluctuations of administered drug doses increase, which may cause not only increasing fluctuation of TAC-C0 but also TAC peak concentrations, which may have a greater impact on adverse allograft outcomes.…”
Section: Introductionmentioning
confidence: 99%